Studi Pengenalan Teknologi Artificial Intelligence Bagi Guru dan Siswa SMK Nurul Islam Larangan - Ginanjar Wiro Sasmito; Dyah Apriliani; M. Nishom (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
SMK Nurul Islam is a vocational high school located in Larangan sub-district, Brebes district, which was founded by the Nurul Islam Slatri educational foundation. Based on the results of an initial survey conducted at partners, that students, teachers, and employees (+- 80%) have heard of the industrial revolution 4.0, but only 30% have heard of Artificial Intelligence. And from the survey, it was found that only 2% have understood and understood Artificial Intelligence technology, which has been applied in almost all sectors of life. The survey results also show that all teachers, employees, and students are familiar with the use of information technology, such as: laptops, smartphones, and the internet. However, the current trend of information technology development is that many do not understand, especially regarding the application of the concept of Artificial Intelligence technology, such as: Face Recognition, Speech Recognition, Expert System, Chatboot, Image Detection, and others. Therefore, community service activities were carried out with the theme Introduction to Artificial Intelligence Technology. The methods of presentation, dialogue and demonstration are carried out in the implementation of these community service activities. Based on community service activities and the comparison between the results of the pre-test and post-test, it is obtained that the knowledge and understanding of partners, namely: students and teachers of SMK Nurul Islam Prohibition on Artificial Intelligence is increasing.